Pelaksanaan Kepemimpinan Ketua Asosiasi Pemerintahan Desa Seluruh Indonesia (APDESI) Di Kecamatan Ketungau Tengah Kabupaten Sintang - Rustandi, Benny; Yohanes, Yulius; Herlan, Herlan (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine and analyze the Leadership of the All Indonesian Village Government Association (APDESI) in Ketungau Tengah District, Sintang Regency and to identify and analyze the factors that become obstacles in the Implementation of the Leadership of the All-Indonesian Village Government Association (APDESI) in Ketungau Tengah District. . This study uses a qualitative method with a descriptive approach. The result of this research is that the implementation of guidance and direction by (APDESI Leader) shows that it is still low, because coaching in the form of guidance has not been carried out continuously. This can be seen from the existence of APDESI adherence in implementing ADEPSI leadership regulations such as violations of working hours and the lack of strict sanctions given such as light warnings while the violations committed are quite severe. The obedience of APDESI in carrying out tasks seems to be still low, because not all APDESI (subordinates) have carried out orders from their superiors perfectly, such as completing tasks not on time that has been determined by their superiors. The leadership of APDESI in carrying out the leadership function of APDESI towards APDESI has not been carried out optimally in strengthening the existence of village government in Ketungau Tengah District, Sintang Regency due to the lack of coordination, facilitation, mediation, and advocacy in the government and village communities. ADEPSI leadership towards the head as a chairperson element in the village government environment, APDESI administrators are required to be able to carry out their duties in accordance with the corridors of the regulations set out in the APDESI articles of association. ADEPSI leadership fostering towards APDESI can empower village governments, village institutions and village communities, forge partnerships and strengthen the position of village existence as the foundation of governance in Indonesia. In implementing to achieve goals, APDESI should carry out the ADEPSI leadership expected by the organization, by paying attention to matters relating to TUPOKSI both by the chairman and members. As well as the APDESI leader in providing action to APDESI members who violate the regulations in the APDESI budget must be carried out strictly to maximize the implementation of village government oriented towards good government (Good Government) in realizing an increase in community welfare in accordance with the hopes and desires of the village community.